1963
DOI: 10.1177/004051756303300106
|View full text |Cite
|
Sign up to set email alerts
|

Heats of Dyeing of Direct Cotton Dyes on Cellulose: A New Thermodynamic Approach to the Determination of Activity of Direct Dyes in Cellulose

Abstract: Heats of dyeing of Chrysophenine G, Cl!lorazol Sky Blue I T , and Congo Red 011 cotton, viscose, and cul)raiiiiiioiiiiiiii rayon have been deterniinetl. It is shown that, except for the initial low concentration of adsorbed dye, the values of heat of dyeing remain more or less the same over a fairly wide range of concentration of adsorbed tlye, and that beyond a critical dye concentration, the values tend to decrease continuously lvlien the proportion of the adsorbed dye is increased. Values for the critical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1968
1968
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The data in suggest that the'dye-fiber interactions are extremely concentration dependent, increasing in magnitude as the dye concentration decreases. This is supported by independent evidence on the apparent heats of dyeing in these systems [3].…”
Section: The Sorplion Nj Anionaic Dyes By Cellulosementioning
confidence: 52%
“…The data in suggest that the'dye-fiber interactions are extremely concentration dependent, increasing in magnitude as the dye concentration decreases. This is supported by independent evidence on the apparent heats of dyeing in these systems [3].…”
Section: The Sorplion Nj Anionaic Dyes By Cellulosementioning
confidence: 52%
“…This may result in decreased accessibility to the functional groups in the amorphous region. As already stated the swelling pressure due to the alkaline solutions can have a large The increase in overall crystallinity is assumed to be responsible for the decreased moisture content (Ant-Wuorinen and Visapaa 1958; Daruwalla and D'Silva 1963). Cellulose II can form hydrates (C 6 H 10 O 5 Á 1/3H 2 O or C 6 H 10 O 5 Á 1/2H 2 O) on sorption of water vapor, but has no water in the unit cell.…”
Section: Pore Structurementioning
confidence: 98%
“…The addition of salt to the dye bath reduces the electrostatic barrier and improves the substantivity, i.e. dye absorption to the fiber (Koh et al 2004;Daruwalla and D'Silva 1963).…”
Section: Fwa Penetrationmentioning
confidence: 99%
“…Since the previous work [28] showed that much better agreement between ex- (The limiting co-area is defined here as the average surface area of cellulose per adsorbed dye anion for a given value of C~)' Thermodynamic values of standard affinity -AlA 0 for the adsorption processes were calculated from the isotherm data by using the following equation which is a modified form of Equation 1. where 9 = ~~ ~ The use of Equation 2 for calcu-[D lating affinities indicates that the activity of the adsorbed dye is defined by the term 1 e ~ [9,10,13] and the mean activity of dye present in the internal cellulose phase i, by the term [at];. If Equation 2 is valid, a plot of log 0 .…”
Section: Equilibrium Adsorption Measurementsmentioning
confidence: 99%